Peningkatan Pemahaman Konsep Bilangan dan Pengukuran melalui Media Konkret Buah Pumpkin pada Siswa Kelas 2 SD - Suwarni Suwarni; Diah Selviani; Dewi Suranti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to improve the understanding of the concept of numbers and measurement through concrete media of pumpkins in grade 2 elementary school students and analyze the process and results of exploration of the concept of measurement and counting carried out by Shelton Elementary School students.. Mathematics education at the Elementary School (ES) level requires concrete media to bridge abstract concepts toward real understanding. The method used is descriptive qualitative, which focuses on in-depth observation and interpretation of phenomena in their natural setting. The pumpkin medium was chosen due to its abundant availability and its relevance to the local autumn context in Colorado, making it a familiar and engaging object for students. This medium was integrated into learning to visualize number concepts (counting seeds), measurement (circumference and weight), and simple arithmetic operations (addition and subtraction). This descriptive qualitative research involved 18 Grade 2 students and 7 parents as volunteers at Shelton Elementary School, Golden, Colorado, USA, on Wednesday, October 22, 2025. Data were collected through participatory observation and field notes on group activities where students performed measurements of the pumpkin's circumference, height, weight, and counted the number of seeds. The results show that the use of the pumpkin medium successfully created a fun and contextual learning atmosphere, increased student motivation, and trained their estimation and actual measurement skills. Interaction with the pumpkin and collaboration with parent volunteers also strengthened students' understanding of number and unit concepts.